PENGAWASAN INSPEKTORAT TERHADAP TUPOKSI CAMAT DI KECAMATAN TAPALANG KABUPATEN MAMUJU - Mukhlis Hannan; Ahmad Saleh (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2018)
This study aims to determine how the inspectorate supervises the Tapalang Sub-district Head of Tupoksi in Mamuju District. This research uses quantitative descriptive techniques that describe quantitatively about supervision carried out by the Office of the Inspectorate to the Tapalang District Head Office, Mamuju Regency. The supervision of the Inspectorate in Tapalang Sub-District of Mamuju District is in empowering the community in accordance with the procedures and is well implemented, including Human Resource Development, Capacity Building in capital, and Development of people's economic institutions. Implementation of supervision of the Inspectorate in the Head of Subdistrict Camat in Tapalang District, Mamuju Regency in the field of tranquility and public order in accordance with the procedures and well implemented and facilitating the implementation of community dispute resolution that has the potential to disrupt peace and public order.